2016
DOI: 10.1002/mus.25145
|View full text |Cite
|
Sign up to set email alerts
|

A population-based survey of risk for cancer in individuals diagnosed with myotonic dystrophy

Abstract: Introduction The risk of cancer in patients diagnosed with myotonic dystrophy (DM) is reported for the homogeneous Utah population. Methods Clinical data accessed from the largest Utah healthcare providers have been record-linked to the Utah Population Database (UPDB), a population-based resource also linked to the Utah Cancer Registry. Relative risks were estimated for 36 cancers of different types in 281 DM patients. Results Testicular cancer (RR=10.74; 95% CI: 1.91, 38.79), endometrial cancer (6.98; 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 15 publications
3
28
0
1
Order By: Relevance
“…(307 DM patients) replicated the elevated risks of thyroid and eye cancer, and suggested a possible testicular cancer risk (SIR = 5.1, P = 0.06) . Two subsequent smaller studies, from France ( n = 109) and the United States ( n = 281), replicated the endometrial cancer finding (both studies), and that of testicular cancer (only the USA study) . The study by Abbott et al .…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…(307 DM patients) replicated the elevated risks of thyroid and eye cancer, and suggested a possible testicular cancer risk (SIR = 5.1, P = 0.06) . Two subsequent smaller studies, from France ( n = 109) and the United States ( n = 281), replicated the endometrial cancer finding (both studies), and that of testicular cancer (only the USA study) . The study by Abbott et al .…”
Section: Resultsmentioning
confidence: 89%
“…Those 4 cancers present a pattern reminiscent of that seen in Lynch syndrome, raising the possibility that an abnormality of DNA mismatch repair may underlie their occurrence. Several subsequent smaller studies validated some, but not all, of the original findings, and suggested the possibility of other affected organs . Inconsistencies between studies regarding specific cancer associations may be due to selection bias in clinic‐based studies, diagnosis misclassification in registry studies, or differences in patient characteristics, such as DM severity or DM subtype.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Published case reports have speculated that patients with DM are at increased risk of benign and malignant tumors, most commonly pilomatricoma (a rare benign calcifying cutaneous neoplasm) . Recent large epidemiological studies have provided evidence that patients with DM are at increased risk of cancers of the endometrium, ovary, eye, thyroid, brain, and testes . Excess risk of colon, lung, and, possibly, melanoma and nonmelanoma skin cancers have also been reported .…”
mentioning
confidence: 99%